SAT0359 The course of mouth opening and its relationship with disease characteristics, global functioning, health-related quality of life and mouth handicap in patients with systemic sclerosis. (15th June 2017) - Khidir, SJH; Boonstra, M; Boerrigter, GWM; Harst, EM Voogt-van der; Bergstra, SA; Ninaber, MK; Marsan, N Ajmone; Huizinga, TWJ; de, JK Vries-Bouwstra
Abstract : Background: Systemic sclerosis (SSc) is a fibrotic disease which can lead to reduced maximal mouth opening (MMO). Previous cross-sectional research showed that reduced MMO in SSc correlated with higher disease severity and lower oral quality of life. Interpretation of interventions that possibly influence MMO is difficult, as the natural history of MMO in SSc is not well described. Objectives: To evaluate in SSc 1) the course of MMO 2) disease characteristics predictive for decreasing MMO and 3) the relationship between the course of MMO and global functioning, health-related quality of life (HRQoL) and mouth handicap. Methods: SSc patients from the Leiden Combined Care In Systemic Sclerosis (CCIS) cohort, Leiden University Medical Center were included if at least one MMO measurement was available. Annual clinical assessment includes MMO measurement, global functioning (HAQ), HRQoL (Short Form-36; SF-36), mouth handicap (Mouth Handicap in Systemic Sclerosis scale; MHISS). We assessed mean MMO, prevalence of microstomia (MMO<30.00 mm) and decreasing MMO (decline >5.00 mm/year) over time. Predictors for decreasing MMO were assessed by a linear mixed model (LMM), including baseline clinical parameters reflecting 7 domains (peripheral vasculopathy, skin, heart, gastrointestinal, lung, renal, musculoskeletal). Additionally, MMO over time was correlated with baseline HAQ, SF-36 and MHISS in separate LMMs adjusted for gender, Body Mass Index, age and disease characteristics correlated significantly ( p <0.05) with the course of MMO. Results: 382 patients were included with mean age 54±14 years, 83% female and 25% diffuse cutaneous SSc. Mean MMO during 6 years of follow-up ranged from 39.4 to 42.5 mm. The annual mean percentage of patients with microstomia was 9%, range 6 to 12% (Figure 1 a). A decrease in MMO between two consecutive annual measurements was observed in 5 to 17% of patients, mean 12% (Figure 1 b). More extended cutaneous involvement, peripheral vasculopathy, pulmonary and gastrointestinal involvement at baseline were predictive for decreasing MMO over time (Table 1 ). Baseline HAQ (β=-1.6, 95% CI=-2.7 to -0.6), SF-36 physical component (β=0.1, 95% CI=0.0 to 0.1) and MHISS (β=-0.2, 95% CI=-0.2 to -0.1) correlated with longitudinal MMO. Conclusions: Over time, MMO is relatively stable in the majority of SSc patients. Microstomia is seen in 9% and important decrease of MMO in 12% and is associated with more severe organ involvement. Even though this concerns only a small subgroup of SSc patients, a significant association with global functioning and HRQoL was demonstrated, underlining the need for treatment strategies improving MMO. Disclosure of Interest: None declared